2017
DOI: 10.3892/ol.2017.6097
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer in cases of multiple primary cancers: Clinical features of 59 cases and point mutation analyses

Abstract: The present study aimed to investigate the occurrence and clinical features of cases of multiple primary cancers including colorectal cancer (MPCC). The medical records of patients with colorectal cancer (CRC) who underwent surgery at the Third Xiangya Hospital of Central South University (Changsha, China) between August 2007 and August 2014 were retrospectively analyzed. Patients with MPCCs were identified and mutation analyses were performed on colon specimens. The results revealed that among 1,311 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…Of these patients, 2 (3.39%) had triple cancer and 1 (1.69%) had quadruple cancer. However, the majority of these were synchronous or metachronous colorectal cancers [6]. In another similar review of 308 cases of colorectal carcinoma, 12 cases of colorectal multiple primary cancers and 14 cases of colorectal primary cancers associated with extracolonic primary cancers were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Of these patients, 2 (3.39%) had triple cancer and 1 (1.69%) had quadruple cancer. However, the majority of these were synchronous or metachronous colorectal cancers [6]. In another similar review of 308 cases of colorectal carcinoma, 12 cases of colorectal multiple primary cancers and 14 cases of colorectal primary cancers associated with extracolonic primary cancers were detected.…”
Section: Discussionmentioning
confidence: 99%
“…recommend extensive molecular profiling in cases with multiple lung cancers, as it might clarify the association between the lung lesions found . Several investigators have reported the utility of molecular biological analysis for diagnosis and treatment in multiple primary cancers, not only in lung cancer but also breast, gastric, hepatocellular, renal, and colorectal cancers . Thus, molecular biological analysis is necessary when multiple cancers of the same histotype are identified in the same tissue where there are multiple primary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio de cánceres primarios múltiples en población China, Wu et al 15 obtiene 1,0% (13/1.311) de cáncer sincrónico extracolónico. Al igual que la casuística coreana, los autores trabajan retrospectivamente con bases de datos poblacionales, y no tienen acceso a la información médica ni exámenes efectuados.…”
Section: Cáncer Sincrónico Extracolónicounclassified
“…Un área muy poco explorada en pacientes con CCR es la existencia de neoplasias sincrónicas extracolónicas. Su incidencia ha sido descrita en escasas publicaciones, y varía entre 0,9% a 4,5% [13][14][15] , aunque las metodologías de búsqueda fueron diferentes, no estandarizadas o no descritas entre las diferentes series, y la mayoría antes del desarrollo de técnicas híbridas como el PET/ CT. Se ha reportado una incidencia de neoplasias sincrónicas extracolónicas en 0,35% de los pacientes asintomáticos sometidos a tamizaje mediante colonoscopía virtual 16 .…”
unclassified